Prevention of Power Theft Using Concept of Multifunction Meter and PLC - Soni, Uma; Kumari, Uma (International Journal of Computer Sciences and Engineering, 2018)
In the system and networks, abnormal behavior is detected by anomaly-based IDS (Intrusion Detection System). If the working of a computer system is different from normal working is considered as an attack. The difference of comparison relies on traffic rate, a variety of packets for every protocol etc. Malicious traffic or data on a system is detected by intrusion detection process. To detect illegal, suspicious and malicious information and data, IDS can be a part of the software or a device. First is Detection of an attack then using different method to stop, Prevent an attack and disaster is the user’s highest priority. Anomaly-based IDS satisfy their requirement and demand.In present scenario electricity theft isa major hurdle in front of government. This problem affects Indian economy. The loss on quantity of theft is mirrored in the electricity company.People are affording more charges because intruders steal electricity by many ways.